2012
DOI: 10.1128/jcm.00972-11
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Methicillin-Susceptible Staphylococcus aureus Related to Sequence Type 25 and Harboring pvl Genes in a Case of Carotid Cavernous Fistula after Community-Associated Sepsis

Abstract: Staphylococcus aureus encoding Panton-Valentine leukocidin (PVL) genes has become the cause of life-threatening infections.We describe a case of carotid cavernous fistula after bacteremia in a 12-year-old male, caused by a methicillin-susceptible S. aureus isolate carrying the pvl, fnbA, and ebpS genes and related to sequence type 25 (ST25). The patient's condition was complicated by pleural empyema and osteomyelitis in the right femur. The patient was discharged in good clinical condition after 160 days of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The genome of CJ16 contains several genes that might be of relevance to skin survival, in keeping with the identity of S. simulans as an opportunistic pathogen. Predicted adhesion proteins involved in colonization and host protein binding, such as autolysin, fibronectin-binding protein ( fnbA ), elastin-binding protein ( ebpS ) ( 15 ), cell wall-anchored protein ( sasA , sasF , and sasH ) ( 16 ), and several additional genes encoding host protein-binding motifs were identified in the genome. Adhesion-encoding genes have been commonly identified in S. aureus isolates, and they have been recognized as being more associated with invasive infections ( 15 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The genome of CJ16 contains several genes that might be of relevance to skin survival, in keeping with the identity of S. simulans as an opportunistic pathogen. Predicted adhesion proteins involved in colonization and host protein binding, such as autolysin, fibronectin-binding protein ( fnbA ), elastin-binding protein ( ebpS ) ( 15 ), cell wall-anchored protein ( sasA , sasF , and sasH ) ( 16 ), and several additional genes encoding host protein-binding motifs were identified in the genome. Adhesion-encoding genes have been commonly identified in S. aureus isolates, and they have been recognized as being more associated with invasive infections ( 15 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…This ST has been detected in bovine and human isolates in the United Kingdom ( 14 ), and an ST25 PVL–positive MSSA was detected in a patient in Brazil with life-threatening sepsis with pneumonia and myositis ( 15 ). ST25 PVL–positive isolates are thought to be rare in Peru: in 2008–2009, only 6 (3.6%) of 169 MSSA blood isolates from hospitalized patients in Lima (non-tropical area of Peru) harbored spa type t078 or related spa types (C. Garcia, unpub.…”
Section: The Studymentioning
confidence: 99%
“…An earlier study on European wildlife identified four isolates among 29 examined animals [ 6 ]. Three were identified as CC425 (a lineage also known from various animals, see below and [ 6 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and one was assigned to CC25 (previously found in humans, [ 46 , 47 , 48 ]). A recent study from Spain [ 49 ] did not identify S. aureus in the twelve badgers examined, and another one from Northern Ireland failed to detect MRSA in badgers [ 50 ].…”
Section: Introductionmentioning
confidence: 99%